Developing Intercultural Competence In Undergraduate Students (2010)
Globalization, understood as a process that has reduced the barriers that separate local contexts from international contexts, has increased and accelerated the economic, cultural, and political interactions among countries, organizations, and citizens (Giddens, 2000). From the business side, firms are increasingly involved in foreign ventures such as outsourcing, off-shoring, exporting, importing and investing in foreign countries that require the correct adaptation of managers to cultural differences. In fact, the inability of managers to face the cultural challenges of doing business abroad is one of the causes of business failures (Johnson, Lenartowicz, & Apud 2006; Black, Mendenhall, & Oddou, 1991). Rather than a lack of ability in the technical aspects of their job, a major factor in business failures (e.g., early return of an expatriate, poor choice of an export market, or problems running a foreign